PENINGKATAN KEAKTIFAN BELAJAR SISWA MELALUI MODEL PJBL BERBANTUAN BUKU MINI SOAL PADA PEMBELAJARAN MATEMATIKA KELAS II SD - Anggraini, Firdalia Lisa; Indawati, Ninik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the lack of student activeness in mathematics learning in grade 2 of SDN Tanjungrejo 2 Malang City. This condition is seen from the behavior of students who tend to be active, but their activeness is not yet directed towards the learning process. As a result, students still have difficulty in focusing their attention during the learning activities. This study aims to improve student activeness through the PjBL model assisted by Mini Question Books. The research method used is Classroom Action Research (CAR) with the Kemmis and Mc Tanggart model. The subjects of this study were 28 grade 2 students. Data collection techniques were observation, interviews, questionnaires, and documentation. The results of the study showed a gradual increase in student learning activeness in the aspects of asking questions, answering, participation/group discussion, and focus/concentration of student learning. In the pre-cycle stage, student activeness was still in the low category. After the application of the learning model in cycle I, there was an increase in the aspect of student activeness, and in cycle II after improvements were made in the form of forming smaller groups, student activeness increased more optimally. The results of this study indicate that the implementation of the PjBL model based on Mini-Problem Books can provide students with meaningful learning experiences. This indicates that the PjBL model assisted by Mini-Problem Books can increase student learning activity in mathematics.